Print and performativity: courtly literature during the Union of the Crowns - Benn, Lisa Elizabeth (2025)
Courtly literature remains the subject of much scholarly debate. Anglo-Scottish courtly literature at the turn of the seventeenth century is further complicated by the Union of the Crowns. Scottish writers seeking to achieve or maintain access to the court had to consider removal to England, whilst English writers were required to navigate a new monarchy with quite different cultural expectations. This thesis examines how writers used literature and circulation to achieve or establish position in this changing political landscape.